Relationship between Policy and Practices of Decision Making in Public Schools - Shiwakoti, Rabindra (Interdisciplinary Research in Education, 2021)
This study is critically analyzed the relationship between policy and practices of decision making in public schools of Nepal. I tried to explore the relationship between policy and practicesin two districts of Kathmandu valley by using qualitative data using power and decentralization theoryand different decision-making models.  I understood that parents, head teacher, and teachers apply decentralization cum power theory in decision making practices in schools. I also found that these authorities mainly take decisions in physical resource management, teacher recruitment, and program extension.  I also came to understand that mixed- model approach is blended between head teacher, teacher and community control model. At the practicing level, I found gap in the use of power in various aspects of decision making.  I also found that these gaps were observed because of practicing of head teacher control model. The study implies that decision making process at the school level needs a new model that must be more contextual and participatory for the effective school management.